Application of time-lapse seismic full waveform inversion method in the detection of karst cave grouting - Xing, Lanjing; Han, Xiaochuan; Bai, Jinliang; Liu, Yaohui; Liu, Lemin; Qu, Chuanqi; Li, Qinggang (Frontiers in Earth Science, 2025)
Grouting is a widely used method for addressing the issue of karst caves in geotechnical engineering. However, the extent and reinforcement effectiveness of grout after injection remain unclear in practical applications. To evaluate the grouting effect in karst caves, time-lapse seismic full waveform inversion (FWI) was employed in a series of field tests in Guizhou Province. The FWI results indicate that the horizontal range of the cave extends from 15 m to 25 m, with a depth range of 6 m–12 m. These findings are consistent with the drilling results, which show a burial depth of 6.2 m–12.4 m. The experimental results demonstrate that FWI can accurately determine the location and size of karst caves. The dispersion energy image of surface waves provides valuable input for the initial FWI model. The karst cave was also detected after grouting, and a wave velocity difference map was obtained. The results suggest that time-lapse FWI is more effective than direct inversion in eliminating the influence of the surrounding environment and highlighting changes in the slurry. The solidification range of the slurry after the second grouting closely matches the shape of the karst cave, suggesting that the cave has been completely filled with slurry. This conclusion is further supported by the drilling and subsequent construction results. Additionally, a comparison of the S-wave and P-wave inversion results shows that S-waves velocity models are more accurate than P-wave ones. These findings provide valuable insights for grouting detection in practical engineering applications.